Condition optimization for electroporation transfection in horse skeletal muscle satellite cells - Tseweendolmaa Ulaangerel; Minna Yi; Undarmaa Budsuren; Yingchao Shen; Hong Ren; Bold Demuul; Dongyi Bai; Dulguun Dorjgotov; Gantulga Davaakhuu; Tuyatsetseg Jambal; Manglai Dugarjav; Gerelchimeg Bou (Animal Biotechnology)
Satellite cells are an important cellular model for studying muscle growth and development and mammalian locomotion-related molecular mechanisms. In this study, we investigated the effects of voltage, pulse duration, and DNA dosage on horse skeletal muscle satellite cells’ electroporation transfection efficiency using the eukaryotic expression plasmid Td Tomato-C1 (5.5 kb) encoding the red fluorescent protein gene mainly based on fluorescence-positive cell rate and cell survival rate. By comparison of different voltages, pulse durations, and DNA doses, horse skeletal muscle satellite cells have nearly 80% transfection efficiency under the condition of voltage 120 V, DNA dosage 7 µg/ml, and pulse duration 30 ms. This optimized electroporation condition would facilitate the application of horse skeletal muscle satellite cells in genetic studies of muscle function and related diseases.